Integrated social studies in the Kurikulum Merdeka: Challenges and strategies - Alvionita Sekar Nur Jayanti; Anik Widiastuti; Taat Wulandari (Curricula: Journal of Curriculum Development, 2025)
While the curriculum faces challenges in disseminating and utilising knowledge, it has led to transformative and empowering experiences for teachers and students. This study aims to identify the challenges encountered in implementing effective strategies and to explore teachers' strategies for addressing them. Integrating social studies into the Kurikulum Merdeka presents challenges and benefits, emphasising the importance of teacher preparedness. Teacher preparedness and continuous training are crucial for the successful implementation of the Kurikulum Merdeka, ensuring it meets the diverse needs of students and prepares them for global challenges. This research uses a qualitative case study approach. Findings reveal three primary challenges: teacher competence, student characteristics, policies, and access to direct learning resources. These challenges can be addressed through strategies such as enhancing teacher capabilities through training, workshops, seminars, and discussions with other educators. Additionally, teachers provide motivation, individualised support, and supervision for students. Teachers can also foster creative learning environments to support adequate social studies education.    Abstrak Meskipun kurikulum menghadapi tantangan dalam penyebaran dan pemanfaatan pengetahuan, penerapannya telah menghasilkan pengalaman yang transformatif dan memberdayakan bagi guru serta murid. Penelitian ini bertujuan untuk mengidentifikasi tantangan yang dihadapi dalam penerapan pembelajaran yang efektif serta menelaah strategi guru dalam mengatasinya. Integrasi pembelajaran IPS dalam Kurikulum Merdeka menghadirkan tantangan sekaligus manfaat, yang menekankan pentingnya kesiapan guru. Kesiapan dan pelatihan berkelanjutan bagi guru menjadi faktor kunci dalam keberhasilan implementasi Kurikulum Merdeka agar mampu memenuhi kebutuhan beragam murid dan mempersiapkan mereka menghadapi tantangan global. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan tiga tantangan utama, yaitu kompetensi guru, karakteristik murid, serta kebijakan dan akses terhadap sumber belajar langsung. Tantangan tersebut dapat diatasi melalui strategi seperti peningkatan kemampuan guru melalui pelatihan, lokakarya, seminar, dan diskusi dengan sesama pendidik. Selain itu, guru memberikan motivasi, pendekatan individual, dan pengawasan kepada murid. Guru juga dapat menciptakan lingkungan belajar yang kreatif untuk mendukung pembelajaran IPS yang optimal. Kata Kunci: kurikulum merdeka; pendidikan IPS; strategi guru; tantangan pendidikan